SEMINAL PLASMA REMOVAL IMPROVES CRYOPRESERVED SEMEN QUALITY IN GADDI BUCKS - SHARMA, A; SOOD, P; DOGRA, PK (The Indian Journal of Animal Reproduction, 2022)
Forty-eight semen ejaculates, collected in artificial vagina, from eight adult Gaddi bucks were randomly divided into groups viz. freezing the entire semen sample (n=24) or removal of seminal plasma by centrifugation (n=24). Semen was extended in tris citrate egg yolk extender to maintain 150 million sperm / dose (0.25 ml). The filling, sealing, equilibration, vapour freezing and final plunging in liquid nitrogen was done as per the standard norms. The post-thaw results (%) of washed semen samples were better (p
Keywords: Buck; Gaddi goats; Semen cryopreservation; Seminal plasma; Washing